A JURIDICAL ANALYSIS OF THE ENFORCEMENT OF LAWS AGAINST ONLINE GAMBLING OFFENSES IN INDONESIA - Hikmal Fahrul Firmansyah; Labib Muttaqin (LPPM STIH Putri Maharaja, 2026)
This study examines the legal issues surrounding the rapid growth of online gambling in Indonesia due to advances in information technology, as well as the challenges faced in enforcing relevant laws. The objective of this research is to analyze the regulation of online gambling under the ITE Law and to evaluate the judge’s legal considerations in Sidoarjo District Court Decision Number 654/Pid.Sus/2023/PN Sda. This study employs a normative juridical method using both a case approach and a legislative approach, relying on secondary data collected through literature review and analyzed qualitatively. The results show that the application of Article 45 paragraph (2) in conjunction with Article 27 paragraph (2) of Law Number 19 of 2016 has been appropriately implemented, as all elements of the offense namely “every person,” “intentionally and without rights,” and the act of distributing or making accessible electronic information containing gambling were fulfilled. However, law enforcement remains constrained by limited supervision and low public legal awareness, which continue to hinder effective implementation of the law.